PERAN KELUARGA DALAM MEMANDIRIKAN ANAK RETARDASI MENTAL DI YAYASAN PEMBINAAN ANAK CACAT MANADO TAHUN 2011 - Johana Tuegeh; Frenny Rompas; Djoni Ransun (Jurnal Ilmiah Perawat Manado (Juiperdo), 2012)
The family is the smallest unit of society is made up of heads of households as well as a few peoplethat get together and live in one roof in a state of interdependence. Each family member has a role toplay. The role of parents affects the child grows.The purpose of this study was Getting a picture of the "Role of Families in independent MentalRetardation Child Development Foundation for Disabled Children in Manado", type of study wasdescriptive. The whole population is taken as a child of parents who have mental retardation in YPAC,while the sampling technique was accidental sampling, held on 19 July 2011 to 28 july 2011 held atthe Foundation for Child Development Disabilities Manado.The results can be concluded that the Role of Families in independent Mental Retardation ChildDevelopment Foundation for Disabled Children in Manado are categorized both by the number ofrespondents 12 people (60%), just 7 people (35%) and less than 1 person (5%). Thus the role of familyin independent foundation coaching children with disabilities in Manado is either disabled child.From these results, the authors recommend for Disabled Children Development Foundation Manadoto increase education about the importance of the role of families in independent mentally retardedchild, so that the role of families to independent of the mentally retarded child can be maintained andfurther improved